Cambial pinning relates wood anatomy to ecophysiology in the African tropical tree Maesopsis eminii. (29th November 2017) - Van Camp, Janne; Hubeau, Michiel; Van den Bulcke, Jan; Van Acker, Joris; Steppe, Kathy
Abstract: A better understanding and prediction of the impact of changing climate on tree stem growth could greatly benefit from the combination of anatomical and ecophysiological knowledge, yet the majority of studies focus on one research field only. We propose an approach that combines the method of pinning (cambial wounding) to timestamp anatomical X-ray computed microtomography images with continuous measurements of sap flow and stem diameter variations. By pinning the cambium of well-watered and drought-treated young African tropical trees of the species Maesopsis eminii Engl. we could quantify wood formation during a specific period of time and relate it to tree physiology and prevailing microclimate. Integrating continuous plant measurements and high-frequency pinning proved very useful to visualize and quantify the effects on stem growth of drought in M. eminii . Wood formation completely stopped during drought, and was associated with a strong shrinkage in stem diameter. Next, an unexpected increase in stem diameter was observed during drought, probably caused by root pressure, but not accompanied by wood formation. Our proposed approach of combining continuous plant measurements with cambial pinning is very promising to relate ecophysiology to stem anatomy and to understand the mechanisms underlying tree stem growth and bridge the gaps between the two research fields.